2001
DOI: 10.1007/s11746-001-0346-4
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of carotenoids in oil systems by a nonporous polymeric composite membrane

Abstract: Earlier studies by the authors on crude vegetable oils showed that color compounds are reduced to the extent of 74-80% during membrane processing. In the present study, attempts were made to understand the rejection mechanism of carotenoids using real and model oil systems. In case of model systems consisting of refined high-oleic sunflower (HOSF) oil, lecithin and β-carotene, the rejection of carotenes was low (11-20%). This could be explained based on the differences between the model and real systems as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…But the greater reduction of color values observed in screw-pressed oils (18) revealed that the solution-diffusion effect was the predominant mechanism in rejecting pigments. It seems that the silicon layer of the membrane did not have higher permeability for xanthophylls, resulting in greater rejection in crude oils (21). HOSF oil along with a lutein and lecithin model system.…”
Section: Table 7 Percentage Reduction and Rejection Of Carotenoids Inmentioning
confidence: 98%
See 4 more Smart Citations
“…But the greater reduction of color values observed in screw-pressed oils (18) revealed that the solution-diffusion effect was the predominant mechanism in rejecting pigments. It seems that the silicon layer of the membrane did not have higher permeability for xanthophylls, resulting in greater rejection in crude oils (21). HOSF oil along with a lutein and lecithin model system.…”
Section: Table 7 Percentage Reduction and Rejection Of Carotenoids Inmentioning
confidence: 98%
“…Xanthophylls (predominantly lutein) were detected in mature soybean seeds, whereas no hydrocarbon carotenoids including β-carotene were detected (except for a trace amounts in some varieties) (32). Xanthophylls are the major carotenoids present in the oils extracted from soybean and rapeseed (21).…”
Section: Rejection Of Carotenoidsmentioning
confidence: 99%
See 3 more Smart Citations